2019–2020 Florida Citrus Production Guide: Root Health Management - Evan G. Johnson; James H. Graham; Kelly T. Morgan (EDIS, 2019)
Developing and maintaining a healthy root system is important for establishment and long-term productivity of trees. Roots take up nutrients and water from the soil to transport them to the tree canopy (the leaves and fruit). The root system also acts as an anchor for the tree, which is important during high wind conditions, such as thunderstorms and tropical systems. At the same time, the leaves provide carbohydrates to grow and maintain a functional root system. In a healthy tree, the carbohydrate supply is balanced between new leaves, fruit, and roots. When root health is compromised, the root system has reduced nutrient and water uptake capacity, which can subsequently affect growth of new leaves and fruit. This 3-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by E. G. Johnson, J. H. Graham, and K. T. Morgan, and published by the Agronomy Department, March 2019.